2020
DOI: 10.3389/fmicb.2020.01932
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Methane on Microbial Communities at Marine Arctic Gas Hydrate Bearing Sediment

Abstract: Cold seeps are characterized by high biomass, which is supported by the microbial oxidation of the available methane by capable microorganisms. The carbon is subsequently transferred to higher trophic levels. South of Svalbard, five geological mounds shaped by the formation of methane gas hydrates, have been recently located. Methane gas seeping activity has been observed on four of them, and flares were primarily concentrated at their summits. At three of these mounds, and along a distance gradient from their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 118 publications
(149 reference statements)
2
29
0
Order By: Relevance
“…Similarly to Vestnesa Ridge, the benthic foraminiferal distribution pattern within the active GHP1 shows a greater variability along the analyzed transect compared to the transect along the inactive GHP5. The highest density of foraminifera is observed at the edge of GHP1, where white and gray bacterial mats are present, with a small difference in density toward the center of GHP1, and reaching zero individuals approximately at the top, where most of the methane flares are located (Serov et al, 2017;Carrier et al, 2020). The δ 13 C DIC value at the top of the active GHP reached −24.2 , which can be linked to methane-related microbial activity (Dessandier et al, 2019).…”
Section: Foraminiferal Faunamentioning
confidence: 96%
See 3 more Smart Citations
“…Similarly to Vestnesa Ridge, the benthic foraminiferal distribution pattern within the active GHP1 shows a greater variability along the analyzed transect compared to the transect along the inactive GHP5. The highest density of foraminifera is observed at the edge of GHP1, where white and gray bacterial mats are present, with a small difference in density toward the center of GHP1, and reaching zero individuals approximately at the top, where most of the methane flares are located (Serov et al, 2017;Carrier et al, 2020). The δ 13 C DIC value at the top of the active GHP reached −24.2 , which can be linked to methane-related microbial activity (Dessandier et al, 2019).…”
Section: Foraminiferal Faunamentioning
confidence: 96%
“…The active GHP1 is characterized by a greater percentage of recently dead (Rose Bengal stained) individuals, compared to living (CHG labeled) specimens, whereas in the inactive GHP5 pingo this ratio is reversed with more live than dead foraminifera. This difference between the active GHP1 and inactive GHP5 implies more unstable and variable environmental conditions at GHP1, potentially related to methane emissions, rather than general seasonal environmental changes (Carrier et al, 2020). On average, CHG labeling showed that approximately 40% of the benthic foraminifera in GHP1 and approximately 54% in GHP5 were alive at the time of collection.…”
Section: Foraminiferal Faunamentioning
confidence: 99%
See 2 more Smart Citations
“…Members of Nanoarchaeota phylum have already been found in hot springs in Yellowstone National Park (United States) under high temperature (~90oC) [64]. They are also associated to volcanoes rich in hydrocarbons [64], deep-sea hydrothermal vents and deep lakes [63][64][65][66][67][68][69][70][71][72][73]. Methermicoccus shengliensis is a methylotrophic methanogen.…”
Section: Taxonomic Affiliation and Phylogenymentioning
confidence: 99%